Smoke control of car parks with electric vehicles - Węgrzyński, Wojciech (Instal, 2021)
The paper contains a comparison of the challenges related to the fires of internal combustion engine vehicles (ICEV) and electric vehicles (EV) in car parks, focused on the issues with effective smoke control. The primary differences were identified in the early growth of fire phase, in which the EV fire can grow faster compared to the ICEV. Results of a multiparametric CFD study are shown, illustrating the role of car park height as the most influential variable related to the safety of the car park occupants.